(untitled) (Journal of Scientific Research, 2014)
A portable HPGe detector has been employed to assess environmental gamma-ray dose following in-situ technique from the primordial radionuclide 40K in the soil at 15 monitoring points (MPs) in the environment at the Atomic Energy Centre, Dhaka (AECD) campus, Bangladesh. The MPs were marked-out using Global Positioning System (GPS) navigation. The measured dose rate due to 40K range from 0.0428 µGy.h-1 to 0.1222 µGy.h-1 with an average of 0.0828 ± 0.0225 µGy.h-1. Keywords: Gamma; Environment; Dose rate. © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v6i2.17146 J. Sci. Res. 6 (2), 285-291 (2014)